2021
DOI: 10.1292/jvms.20-0518
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal basaloid carcinoma arising from thymic cysts in two dogs

Abstract: Mediastinal masses in dogs were diagnosed as basaloid carcinoma associated with multiple thymic cysts (MTCs). The masses were composed of MTCs and proliferating intracystic neoplastic basaloid cells, which immunohistochemically diffusely expressed p63 and cytokeratin 19. A gradual transition from the basal cell layers lining the cysts walls to the neoplastic cells was seen, and it was indicated that the neoplastic cells had originated from the basal cell layers of the cysts. To the best of our knowledge, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a study summarizing several cases of pharyngeal remnant cysts, including one found in the cranial mediastinum, authors found varying types of epithelium, but all cases had cilia 19 . More authors have justified a thymic or branchial cyst diagnosis based on the presence of partially to fully ciliated epithelial cells in the cyst lining 20 . In summary, our diagnosis of bronchogenic cyst is supported histologically by the presence of ciliated pseudostratified epithelium and mucus within the cyst lumen.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a study summarizing several cases of pharyngeal remnant cysts, including one found in the cranial mediastinum, authors found varying types of epithelium, but all cases had cilia 19 . More authors have justified a thymic or branchial cyst diagnosis based on the presence of partially to fully ciliated epithelial cells in the cyst lining 20 . In summary, our diagnosis of bronchogenic cyst is supported histologically by the presence of ciliated pseudostratified epithelium and mucus within the cyst lumen.…”
Section: Discussionmentioning
confidence: 80%
“…19 More authors have justified a thymic or branchial cyst diagnosis based on the presence of partially to fully ciliated epithelial cells in the cyst lining. 20 In summary, our diagnosis of bronchogenic cyst is supported histologically by the presence of ciliated pseudostratified epithelium and mucus within the cyst lumen. It is evident future studies are needed to develop a consensus on histologic criteria for bronchogenic cysts when compared to other thymic cysts.…”
Section: Discussionmentioning
confidence: 84%